El impacto de los mercados atlánticos en la evolución del olivar en el Reino de Sevilla durante la Edad Moderna - Mercedes Gamero Rojas (Erebea. Revista de Humanidades y Ciencias Sociales, 2015)
Oil was one of the most productive crops in Lower Andalusia during the modern era due to its multiple uses. It was not only destined to its consumption and other domestic uses, but had an industrial use in soap factories and wool washing places. It was this latter circumstance that made it dependent on the needs of the inner and outer draperies and on the circumstances of foreign policy, with its sequences of prohibitions, seizures and permissions. In this paper, we study the evolution of the olive grove in the Kingdom of Seville during the aforementioned period, and its various internal rhythms. Urban capital investment in the countryside produced the concentration of ownership and the evolution of the landscape, thanks not only to the new plantings but also to the building of new olive farms, with their graceful profile of towers and viewpoints.